Kemampuan Guru dalam Melaksanakan Pembelajaran PAI dengan Pendekatan Saintifik Learning pada Kurikulum 2013 di SMP Bina Siswa Kabupaten Deli Serdang - Neliwati, Neliwati; Rahman, Anisa Hayati; Raudhoh, Fiza; Angraini, Tiara; Rambe, Yusuf Hamdani (MODELING: Jurnal Program Studi PGMI, 2023)
The problem analyzed in this study is the teacher's ability to carry out PAI learning with a scientific learning approach in the 2013 curriculum at SMP Bina Siswa, Deli Serdang Regency. This research was conducted with the aim of describing the problems faced by PAI teachers at SMP Bina Students in Deli Serdang Regency in the application of scientific learning-based learning to PAI learning. The research method used is using qualitative research methods and descriptive approaches. This research was conducted at SMP Bina Siswa, Deli Serdang Regency, using data collection techniques in the form of observation, interviews, documentation and library research. The subjects of the study were school principals, Islamic religious teachers and several student representatives from grades 7 to 9 at SMP Bina Siswa, Deli Serdang Regency. The results of the research obtained are: (1) Teachers who teach PAI subjects at Bina Siswa Middle School still experience difficulties in planning the implementation of learning, because the rules that change frequently make teachers confused, so there are teachers we study who still use lesson plans. long. Policies that often change also make teachers who initially understand do not understand anymore and have to learn from the beginning. (2) PAI teachers who do not understand the concept of a scientific approach, so PAI teachers have difficulty presenting material for students to easily understand, sometimes they often find it difficult to manage classes which are part of class management skills. (3) PAI teachers at SMP Bina Siswa, Deli Serdang Regency, still use a conventional approach in the learning process, learning activities use approach considering the teacher.